PEMAHAMAN MAHASISWA TERHADAP PENTINGNYA VAKSINASI SEBAGAI PENCEGAHAN COVID-19 - Vevi Kurniawati (Akper Kesdam I/Bukit Barisan Padang, 2021)
The current situation of Covid-19 is still increasing, including in Indonesia. Covid-19 is a disease caused by infection with Coronavirus which is a new type of virus that causes respiratory tract diseases. Various efforts to prevent the spread of the virus continue to be carried out, one of the way through vaccination. The purpose of this study was to determine students' understanding of the importance of vaccination as a prevention of Covid-19. This research method is descriptive which presents an overview of students' understanding of the importance of vaccination as a prevention of Covid-19, The population in this study was 132 students, sampling using the Slovin’s formula, obtained a sample of 99 respondents. Research results on student understanding of the importance of vaccination as an effort to prevent Covid-19, most students have an understanding of the Good category as many as 74 students (74.8%), Enough category as many as 17 students (17.2%), and understanding in the Poor category as many as 8 students (8%). It is hoped that with a good understanding of students, they can help the Government in efforts to prevent Covid-19.